2021
DOI: 10.1155/2021/6690658
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Systemic Lupus Erythematosus and Antineutrophil Cytoplasmic Antibodies-Associated Vasculitis Overlap Syndrome

Abstract: An overlap of systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic antibodies- (ANCA-) associated vasculitis (AAV) is extremely rare: approximately 40 cases have been reported to date. A literature review indicates that they are more common in women in their forties, and simultaneous onset has been reported in 69% of cases. In addition, both lupus nephritis and ANCA-associated glomerulonephritis were observed on renal biopsy. This report presents the case of a 35-year-old woman with an 8-month his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Usually, LN develops within the first three years following the diagnosis of SLE [ 9 ]. Testing for anti-dsDNA, anti-C1q autoantibodies, and complement levels (C3 and C4) should be considered in patients with suspected LN [ 7 ]. Levels of anti-ds DNA Ab reflect disease presence and activity in patients with LN [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, LN develops within the first three years following the diagnosis of SLE [ 9 ]. Testing for anti-dsDNA, anti-C1q autoantibodies, and complement levels (C3 and C4) should be considered in patients with suspected LN [ 7 ]. Levels of anti-ds DNA Ab reflect disease presence and activity in patients with LN [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the overlap of LN and AAV is mostly present in women of child-bearing age who present with severe clinical presentation, including severe renal impairment. Renal biopsy tends to reveal a mixed involvement of immune complex-mediated renal injury, as seen in LN, and evidence of necrotizing and crescentic glomerulonephritis, as seen in AAV [ 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overlap syndrome is a connective tissue disorder that meets the criteria for at least two known autoimmune diseases [ 4 ]. The concomitant presentation of both SLE and AAV as overlap syndrome is rare, with only a few cases have been reported in the past [ 5 ]. Here, we present a rare case of subarachnoid hemorrhage as an initial presentation of SLE-AAV overlap syndrome.…”
Section: Introductionmentioning
confidence: 99%